Nurse Driven Pediatric Triage: Modified for Developing Country - M. Johnson (Current Practice in Medical Science Vol. 2, 2022)
Children represent the most vulnerable population. And moreover the deaths among those in hospitals often occur within 24 hours of admission. If very sick children are identified soon and the treatment is initiated death can be prevented. Triage is a quick assessment to prioritize patients upon presentation to the emergency department (ED), according to the acuity of their presenting condition. The word triage comes from the French word “Trier” that literally means to sort. The objective of triaging is to ensure that right patient gets right treatment at the right time. The commonly used triage system for developing country according to WHO pocket book of hospital care for children. During this COVID pandemic nurses especially play a vital role in the assessment through triaging and management of the children ensuring quality nursing care.